2006
DOI: 10.1159/000095362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Vascular Calcification and QT Interval in ESRD Patients: Is There a Link?

Abstract: We will present our experience and our preliminary data about the correlation between cardiac calcification and QT interval (and QT dispersion) in uraemia. We studied 32 haemodialysis (HD) patients (age 69 ± 16 years, time on dialysis 32 ± 27 months) and 12 chronic kidney disease stage 4 (CKD-4) patients (age 66 ± 17 years, uraemia duration 38 ± 16 months). The patients were characterized by a good mineral control, as shown by serum phosphate levels (3.6 ± 1.3 mg/dl in CKD-4 and 4.3 ± 1.6 mg/dl in HD patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 90 publications
2
20
0
Order By: Relevance
“…Previous cross-sectional studies have already documented that VCs are closely associated with arterial stiffness [10,19] and in a previous paper we found an association between CAC and QTd [14] . However, these analyses add to the existing body of evidence by confirming these associations in a longitudinal study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Previous cross-sectional studies have already documented that VCs are closely associated with arterial stiffness [10,19] and in a previous paper we found an association between CAC and QTd [14] . However, these analyses add to the existing body of evidence by confirming these associations in a longitudinal study.…”
Section: Discussionsupporting
confidence: 67%
“…It has been suggested that QTd reflects heterogeneity of myocardial repolarization and predicts poor all-cause and CV survival independently on traditional CV risk factors in CKD-5 [27][28][29][30][31][32][33] . In a previous paper we showed an independent association between CAC and QTd, suggesting that subclinical vasculopathy might also be related to cardiac electrical impairments [14] . In this perspective, a couple of studies from the general population deserve mention.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Di Iorio et al [14] found an association between QT dispersion, but not QTc interval duration and arterial calcifications. However, the study included patients at different stages of CKD and was hampered by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Claes et al [1] affirm that 'to the best of our knowledge, only one study so far has reported on the association between QT duration and arterial calcification in renal patients'. Di Iorio et al [2] found an association between QT dispersion (QT-d), but not QT-c interval duration and arterial calcifications. However, the study included patients at different stages of CKD and was hampered by the small sample size.…”
mentioning
confidence: 99%